Pengujian Black Box pada Aplikasi Berita Online dengan Menggunakan Metode Boundary Value Analysis - Ahmad Ijudin; Aries Saifudin (Jurnal Informatika Universitas Pamulang, 2020)
Testing is one level that must be passed in order to produce results from a weighted system. If no testing is done on the system, the quality of the system cannot be known so that if an error occurs it can harm the system. By conducting experiments can find the location of defects in a system that can be known from the beginning that can be fixed immediately. Testing there are several types of system experiments, experiments used are black box testing using a limit value analysis method that is effective in trying the functions of a system. The technique determines the limits on the lower and upper values to produce the actual values. Based on the test results using the boundary value analysis technique that still has a disability that is the lack of data verification, then there must be an improvement in the validation function.